Social networking in recruiment build your social networking expertise to give yourself a cost-effective advantage in the hiring market - Belton, Amanda (Impackt Publishing, 2014)
This book is for hiring manager or HR professioanl who looking to update the skills and give the organization a competitive advantage in the hiring market.